2017
DOI: 10.1038/ismej.2017.51
|View full text |Cite
|
Sign up to set email alerts
|

Denitrifying community in coastal sediments performs aerobic and anaerobic respiration simultaneously

Abstract: Nitrogen (N) input to the coastal oceans has increased considerably because of anthropogenic activities, however, concurrent increases have not occurred in open oceans. It has been suggested that benthic denitrification in sandy coastal sediments is a sink for this N. Sandy sediments are dynamic permeable environments, where electron acceptor and donor concentrations fluctuate over short temporal and spatial scales. The response of denitrifiers to these fluctuations are largely unknown, although previous obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
109
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 127 publications
(116 citation statements)
references
References 79 publications
5
109
2
Order By: Relevance
“…S5). These results agree with previous reports ( Ji et al., ; Marchant et al., ; Castellano‐Hinojosa et al., ) and lend support to the existence of denitrification under aerobic conditions. In contrast to DMPP, no increases in the abundance of norB and nosZ I during the incubation time were observed in soils treated with urea + NBPT, which suggest an effective temporal effect of NBPT on denitrifiers.…”
Section: Discussionsupporting
confidence: 93%
“…S5). These results agree with previous reports ( Ji et al., ; Marchant et al., ; Castellano‐Hinojosa et al., ) and lend support to the existence of denitrification under aerobic conditions. In contrast to DMPP, no increases in the abundance of norB and nosZ I during the incubation time were observed in soils treated with urea + NBPT, which suggest an effective temporal effect of NBPT on denitrifiers.…”
Section: Discussionsupporting
confidence: 93%
“…Few trends could be seen across the tidal cycle when the different genes were examined individually ( Fig. 4 and see Marchant et al, 2017). This suggests that there is no strong response at the transcriptional level to the large fluctuations that occur over a day at the sand flat.…”
Section: Production and Consumption Of Denitrification Intermediates mentioning
confidence: 98%
“…Previous studies have shown that oxygen can penetrate more than 5 cm while the tide is in, and while the tide is out only penetrates 1-2 cm (see Marchant et al, 2017, Jansen et al 2009. Sediment was collected from the upper 5 cm of the sand flat and stored in washed plastic containers for transport before use in steady state core incubations, dynamic core incubations and microsensor experiments.…”
Section: Study Site and Samplingmentioning
confidence: 99%
See 1 more Smart Citation
“…This observation cannot easily be explained by the presence of denitrification under oxic conditions. We note that our maximum rate of denitrification under bulk oxic conditions measured in the FTR reactors (4.6 µmol N L −1 h −1 ) is at the lower end of denitrification rates reported under oxic conditions in silicate sands of ∼ 6-17 µmol N L −1 h −1 (Gao et al, 2010;Marchant et al, 2017), suggesting that denitrification under oxic conditions, where it occurs, has a greater enhancement effect on total denitrification than denitrification in anoxic microniches.…”
Section: Denitrification Within Carbonate Sand Grainsmentioning
confidence: 91%